2008
DOI: 10.1007/s11064-008-9803-9
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-Induced Regulation of CD95(Fas) Expression in the N9 Microglial Cell Line: Evidence for Involvement of Proteinase-Activated Receptor1 and Extracellular Signal-Regulated Kinase 1/2

Abstract: Microglia are the immune cells of the CNS. Brain injury triggers phenotypic changes in microglia including regulation of surface antigens. The serine proteinase alpha-thrombin can induce profound changes in neural cell physiology via cleavage of proteinase-activated receptors (PARs). We recently demonstrated that pharmaceutical-grade recombinant human alpha-thrombin (rh-thr) induces a restricted set of proteolysis-dependent changes in microglia. CD95(Fas) is a cell-death receptor that is up-regulated in microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…To our knowledge, this is the first report of PAR-1 cleavage by MMP-3, MMP-8, or MMP-9. A recent report showed that thrombin (a ligand of PAR-1) induced CD95 expression via PAR-1 activation in N9 microglial cells (32). Interestingly, the sites of PAR-1 cleavage by MMP-3, -8, and -9 were the same as those of thrombin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To our knowledge, this is the first report of PAR-1 cleavage by MMP-3, MMP-8, or MMP-9. A recent report showed that thrombin (a ligand of PAR-1) induced CD95 expression via PAR-1 activation in N9 microglial cells (32). Interestingly, the sites of PAR-1 cleavage by MMP-3, -8, and -9 were the same as those of thrombin.…”
Section: Discussionmentioning
confidence: 93%
“…During our search for cell surface receptors involved in MMP-mediated microglial activation, we noted that PAR-1 had been reported to mediate MMP-1-induced endothelial activation and tumorigenesis and thrombin-induced microglial activation (31,32). Thus, to test the possible involvement of PAR-1 in a-synuclein-induced microglial activation, FIGURE 4.…”
Section: Par-1 Inhibitors Suppressed A-synuclein-induced Microglial Amentioning
confidence: 99%
“…Although the physiological significance of this upregulation remains to be determined, it is interesting to note that over the past years, several studies have suggested the involvement of microglial PARs, especially PAR-1, in the balance of inflammatory processes in the nervous system (Weinstein et al 2008;Weinstein et al 2009). In particular, our group has observed that the administration of PAR-1 activating peptides (TRAP6 and TFLLR) inhibits the production of the proinflammatory cytokines TNF-α and IL-6 in microglial cells treated with lipopolysaccharide, while promoting the release of the anti-inflammatory cytokine IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…To detect the mRNA expression of Fcα/μR in mouse microglia, RNA isolation (including on-column DNase digestion), reverse transcription and quantitative Real-Time polymerase chain reaction (qRT-PCR) were done as previously described (28). In brief, qRT-PCR was performed using the 7500 Real Time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%